2011
DOI: 10.1111/j.1743-6109.2011.02354.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperthyroidism: A Risk Factor for Female Sexual Dysfunction

Abstract: Introduction Hyperthyroidism is a common hormonal disorder in women that may cause female sexual dysfunction (FSD). Aim To assess sexual function in women with hyperthyroidism. Methods A total of 40 women with clinical hyperthyroidism and 40 age-matched voluntary healthy women controls were included in the study. All the subjects were evaluated with a detaile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Alternative biomarkers to assess the supply of the organism with thyroid hormones include resting heart rate and other determinants of cardiac output [384, 385], oxygen consumption [386, 387], respiratory quotient [388, 389], thermogenesis [26, 390392], methylhistidine excretion [393397] and plasma levels of lipids [398, 399], SHBG [400405], sclerostin [406], ceruloplasmin [407], lead [408], copper [407–410], arsenic [408], or MBL [411, 412]. These parameters have not been well evaluated, however, and due to the fact that they are subject to multiple extrathyroidal influencing factors they are not expected to deliver superior results as diagnostic tools.…”
Section: The Tsh Reference Range—an Ongoing Controversymentioning
confidence: 99%
“…Alternative biomarkers to assess the supply of the organism with thyroid hormones include resting heart rate and other determinants of cardiac output [384, 385], oxygen consumption [386, 387], respiratory quotient [388, 389], thermogenesis [26, 390392], methylhistidine excretion [393397] and plasma levels of lipids [398, 399], SHBG [400405], sclerostin [406], ceruloplasmin [407], lead [408], copper [407–410], arsenic [408], or MBL [411, 412]. These parameters have not been well evaluated, however, and due to the fact that they are subject to multiple extrathyroidal influencing factors they are not expected to deliver superior results as diagnostic tools.…”
Section: The Tsh Reference Range—an Ongoing Controversymentioning
confidence: 99%
“…A single study has investigated female sexual function in acromegaly patients (22) using FSFI. SD was present in 68% of patients with acromegaly compared to 28% of healthy women, and all FSFI domains scores were significantly lower in acromegalic patients than among controls (22) (25,27,28), whereas it is higher -around 44-60% -in hyperthyroidism (29,30,31).…”
Section: Increased Ghmentioning
confidence: 93%
“…In the last few years, different papers showed a correlation between hyperthyroidism and SD in women with case control studies (29,30,31,35) (Table 3). Their major limitation is the fact that these are small studies, but they all showed the same result, therefore confirming the association between clinically-evident thyroid pathology and SD.…”
Section: Hyperthyroidismmentioning
confidence: 99%
“…65 Overt [66][67][68] or subclinical 66,69 hypothyroidism and hyperthyroidism have been associated with reduced sexual desire. 68,70 Conversely, polycystic ovary syndrome is often characterized by clinical and/or biochemical signs of hyperandrogenism, with or without oligoovulation or anovulation, or polycystic ovaries. Women with polycystic ovary syndrome have psychological (feeling less attractive, less feminine, more depressed) and biological (obesity and infertility) factors that may negatively influence their sexual desire.…”
Section: Modifiable Factorsmentioning
confidence: 99%